Development of Mosque Accounting Information Systems Based on Non-profit Entity Reporting Standards and Sharia Compliance: A Case Study at the X Great Mosque - Asrori, Asrori; Kiswanto, Kiswanto; Fachrurrozie, Fachrurrozie; Amal, Muhammad Ihlashul (Jurnal Dinamika Akuntansi, 2020)
The mosque, a place of worship for Muslims, is a non-profit entity that receives public funds. The mosque should manage, record, and report the receipt and use of mosque funds in an Islamic and accountable manner. This study aims to identify and develop a mosque accounting information system that is per the reporting standards of non-profit organizations and meets sharia compliance. The observed object of this study (hereinafter referredÃ‚Â to the X Great Mosque) is one of the great mosques in Central Java Province. This study employs qualitative methods, a case study approach, with data sources of seven participants, including treasurer, secretary, accounting and financial staff, the heads of ketakmiran, education, and social, assets and maintenance, and business affairs programs. This study found that the X Great Mosque carries out accounting information systems properly according to the reporting standards of the non-profit organization. However, the accounting information system at the X Great Mosque, as part of Islamic accounting, has not fully met Sharia compliance because it has not separated in recording and reporting the restricted and unrestricted funds.Ã‚Â